Utilization of iodized salt in the production of smoked tunsoy - Pujanes, Kristina Maureen Ogali
The general objective of this study is to determine the effect of using iodized salt on the quality of smoked tunsoy. This is in response to the ASIN law(An Act Promoting Salt Iodization Nationwide and Related Purposes) legislated by the government last December 20, 1995 to help alleviate Iodine Deficiency Disorders (IDD) problem in the country. This law requires food manufacturers and processors to use iodized salt in the processing of their products. The first phase of the study involved the selection of a commercial process producing an acceptable smoked tunsoy. Among three participating local commercial producers of smoked tunsoy in the study, the process employed by Mrs. Baby Caluag or Processor 2 was the most acceptable based on objective and sensory analyses. Physico-chemical tests of the samples obtained from Processor 2 gave the following results: pH 7, aw of 0.895 and 1.12% salt content. The samples showed an average total plate count of 2.4 x 10^5 and a yeast and mold count of 2.11 x 10^4 cfu/g. In the consumer acceptability test, samples from Processor 2 were described to have a golden brown color, neither smooth nor flaky surface appearance, smoky aroma and taste, moderately salty, firm but easy to chew and neither moist nor dry. In the second phase of the study, smoked tunsoy were produced employing the process of Processor 2. One lot was prepared with iodized salt, the other with unfortified salt. Smoked tunsoy produced in the second phase were subjected to quality assessment in the third phase of the study. Results of the physico-chemical tests of smoked tunsoy with iodized salt showed a slightly higher pH of 6.0, lower aw of 0.93 and lower %NaCl of 0.93%. Microbiological tests showed a total plate and yeast and mold counts of 8.6 x 10^3 and 3.5 x 10^2, respectively, for the smoked tunsoy prepared with iodized salt. The iodine content of the unfortified and iodized salts were 4.6 and 62.1 μg/g, respectively. The iodine content of fresh tunsoy was 1.53 mg/g. An increased of up to 2.49 mg/g salted fish was recorded after brining with iodized salt. Boiling caused a reduction of this iodine content to 1.14 mg/g fish. Smoking further reduced this iodine content to 0.66 mg/g. Results of the sensory evaluation using paired difference test between the smoked tunsoy samples prepared with iodized salt and its control showed no significant difference between the samples at 5% level of significance.